Public health and human values - Häyry, M (BMJ Group, 2006)
The ends and means of public health activities are suggested to be at odds with the values held by human individuals and communities. Although promoting longer lives in better health for all seems like an endeavour that is obviously acceptable, it can be challenged by equally self‐evident appeals to autonomy, happiness, integrity and liberty, among other values. The result is that people's actual concerns are not always adequately dealt with by public health measures and assurances.